REAKSI PASAR MODAL INDONESIA TERHADAP KESEPAKATAN INVESTASI ANTARA PEMERINTAH INDONESIA DENGAN PEMERINTAH ARAB SAUDI - Kartika Wijaya; Hendra Gunawan (Politeknik Negeri Batam, 2019)
This research is an event study which aims to analyze the difference of abnormal return and trading volume activity of whole Indonesian Stock Exchange stocks before and after a political event occurring in the country. The object of observation was the announcement of the investment agreement between the Indonesian government and the Saudi Arabian government on March 01, 2017 using indicators of abnormal return and trading volume activity. Population and sample in this research are all the companies listed in Indonesian Stock Exchange, which are 539 companies. The data used are secondary data of daily closing stock price, IDX composite, daily trading volume and the number of outstanding stocks starting from February 01 to March 29, 2017. The statistical test used to test the hypothesis is paired sample t-test. The results showed that: (1). The investment agreement between the Indonesian government and the Saudi Arabian government has a positive insignificant effect on abnormal return of all IDX stocks simultaneously for the observation period days of 12th, 11th, 09th and 01st. (2). The investment agreement between the Indonesian government and the Saudi Arabian government also has a positive insignificant effect on trading volume activity of all IDX stocks simultaneously for the observation period days of 19th, 18th and 12th.